Study the Motivation that Affect the Work Performance of Employees in the North Region Power System Management Department of the Lao PDR - philabuon, salongsay; Kounlaxay, Kalaphath; Orphomma, Sounith (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objective of this study was to motivation that affect the work performance of employees in the Northern Region Power System Management Department of the Lao PDR. A quantitative study was used to ask the opinions of 308 employees. The statistic used to analyze the data was the multiple regression correlation coefficient with a statistical significance level of 0.05. By the power of motivational and the power of supporting factors analyzed included 11 indicators, including: job security (X1), recognition (X2), job characteristics (X3), job responsibility and achievement (X4), career advancement (X5), compensation (X6), welfare (X7), policy and management (X8), relationship with superiors and colleagues (X9), work environment (X10), management methods (X11), and the focus on employee performance that was analyzed included 3 aspects: 1. Job satisfaction (Y1), 2. Creative initiative (Y2) and 3. Work efficiency (Y3). The results of the analysis found that the power of motivational and the power of supporting factors analyzed had 11 indicators that were correlated with (Y1), (Y2) and (Y2) at a low level and 11 power of motivational and the power of supporting factors in total (X) which found that only 1 aspect: the job security that affected the work performance of employees in the Northern Region Power System Management Department of the Lao PDR for creative initiative (Y2) and work efficiency (Y3), while the work performance in terms of job satisfaction (Y1) was not effective. Therefore, the remaining 10 motivational and supportive do not effect on the work performance in the Northern Region Power System Management Department. As a result, the motivation in this area is not performing as well as it should, so it should be improved and resolved. Although there are some aspects that affect the performance of their work, they are still at a low level.